Psychoonkologische Versorgung in Stadt und Land: Erfahrungen und Wünsche von Krebspatienten und deren Angehörigen - Hartmann, Mechthild; Haun, Markus W.; Sklenárová, Halina; Zimmermann-Schlegel, Verena; Herzog, Wolfgang (Der Onkologe, 2017)
Background. The diagnosis of cancer is frequently accompanied by signiﬁcant psychosocial distress not only for patients but also for their caregivers. Psycho-oncological services are nowadays implemented in routine oncological care to address such needs; however, little is known about utilization of psychosocial support by patients and caregivers outside of cancer centers. Objective. The aim of the study was to establish whether there is suﬃcient coverage and adequate use of psycho-oncological services in cancer survivors living in rural areas. Additionally, we were interested in the number of caregivers who received any form of psycho-oncological care.